2017
DOI: 10.1002/ppul.23915
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐inflammatory mediator responses from neonatal airway epithelial cells and early childhood wheeze

Abstract: Background: Airway epithelial cell (AEC) function differs between children with and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…There are limited data on airway epithelial cell function at birth and later wheeze outcomes. In one study, nasal epithelial cells were harvested in newborns as a surrogate for the lower airway (47). They were followed up by parental questionnaire to determine wheeze outcomes.…”
Section: The First Steps: Episodic Viral Wheezementioning
confidence: 99%
“…There are limited data on airway epithelial cell function at birth and later wheeze outcomes. In one study, nasal epithelial cells were harvested in newborns as a surrogate for the lower airway (47). They were followed up by parental questionnaire to determine wheeze outcomes.…”
Section: The First Steps: Episodic Viral Wheezementioning
confidence: 99%
“…Impaired epithelial antiviral responses, with reduced interferon-β production and increased viral replication in response to human rhinovirus (HRV) [52] and respiratory syncytial virus (RSV) [53] infection has also been shown in children with wheeze/asthma in vitro. Similar responses in airway epithelial cells sampled from neonates in the first 48 hours of life prior to wheeze onset [54] suggest a potentially important role of altered airway epithelial cell function in the development of wheezing. One of the characteristic pathological features of established asthma, apparent in school-age children, is airway remodeling.…”
Section: The Airway Epithelium and Structural Cells In Preschool Wheezementioning
confidence: 81%
“…Airway epithelial cells. Neonatal cells will be cultured at air liquid interface to achieve a differentiated epithelial cell layer and, as previously 12 , responses to common environmental exposures will be compared between those who have asthma symptoms and those who have no asthma symptoms by three years of age. RNA will also be extracted from cells and a particular focus will be genes involved in tissue proliferation, repair and remodelling.…”
Section: Methodsmentioning
confidence: 99%
“…Two systematic reviews have described many differences between the characteristics of AEC from children with and without asthma 10 , 11 . One proof-of-concept study described differences in neonatal nasal AEC function for individuals who went on to have asthma symptoms at age four years compared to those who did not 12 . This study 12 also observed that not all individuals with abnormal neonatal AEC function went on to have asthma symptoms, suggesting that asthma requires both abnormal neonatal AEC function and at least one other factor.…”
Section: Introductionmentioning
confidence: 99%